Gasification for Low-Grade Feedstock 2018
DOI: 10.5772/intechopen.74485
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of Plasma Gasification Technologies for Hazardous Waste Treatment

Abstract: The chapter is devoted to the development of technologies for the processing of carbonaceous wastes, including hazardous ones, using plasma energy sources. In particular, plasma-steam equipment provides complete environmental safety and high quality of the synthesis gas produced. Its application is also discussed to exclude the risk of environmental pollution by heavy metals, if they are contained in the recycled waste. The advantages of using oxygen instead of air as an additional reagent in gasification proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 21 publications
(45 reference statements)
0
8
0
Order By: Relevance
“…2024, 14, 4801 3 of 14 stored in landfills or used as a secondary raw material in production. Vitrification using plasma pyrolysis has been found to reduce environmental costs [1][2][3][28][29][30].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2024, 14, 4801 3 of 14 stored in landfills or used as a secondary raw material in production. Vitrification using plasma pyrolysis has been found to reduce environmental costs [1][2][3][28][29][30].…”
Section: Methodsmentioning
confidence: 99%
“…Such compounds are stable, so their impact on the environment is imperceptible, and they can be safely stored in landfills or used as a secondary raw material in production. Vitrification using plasma pyrolysis has been found to reduce environmental costs [1][2][3][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Zhovtyansky and Valinčius [96] have done an extensive study on plasma gasification of waste and concluded it to be a commercially viable alternative based on the ecological benefits it possesses and the total energy efficiency of the system. Plasma gasification is highly efficient in treating hazardous waste, with an efficiency of 99.9%.…”
Section: Plasma Gasification Treatment Of Biomedical Wastementioning
confidence: 99%
“…This process offers several advantages, including the efficient destruction of organic pollutants, the reduction of waste volume and mass, and energy recovery [6][7][8]. Due to the high temperatures and rapid product quenching, thermal plasma gasification minimizes the formation of toxic compounds during waste treatment [9]. Utilizing this technology, sewage sludge can be decomposed into two primary products: combustible synthesis gas and inert glassy slag, providing significant environmental benefits in terms of atmospheric emissions and slag toxicity control [6].…”
Section: Introductionmentioning
confidence: 99%
“…However, as plasma gasification is a relatively new technology, there are still gaps in our understanding of its performance and characteristics. Additionally, sewage sludge gasification also presents challenges [9,10], mainly due the heterogeneity of this raw material. Some of these challenges are presented by Gao et al [11], such as the low heating value (LHV) of the material, the cold gas efficiency (CGE), the carbon conversion efficiency (CCE), the greenhouse gas emissions, the high levels of ash production, the high energy costs due to the need for moisture reduction prior to gasification, and the requirement to recover phosphorus (P), nitrogen (N), and potassium (K) from the ash [11].…”
Section: Introductionmentioning
confidence: 99%